Budaya Manugal Sebagai Suatu Kearifan Lokal Masyarakat Dayak Desa Buntut Bali Kecamatan Pulau Malan Kabupaten Katingan - Joko Candra; Muhamad Safwan; Hadiatma H.B; Elsy. C.M Pasaribu; Ahmad Saefulloh (Universitas 45 Surabaya, 2023)
The research topic discussed is Manugal Culture as a Local Wisdom of the Dayak Community, Buntut Bali Village, Malan Island District, Katingan Regency. This study aims to find out the origins of manugal culture, the time and process of manugal culture and the meaning of manugal culture for the Dayak Community in Buntut Bali Village, Malan Island District, Katingan Regency. The objects in this study were all the people involved in the research. The research method used is a qualitative inductive method. The research instruments included: observation sheets, interviews to find out manugal culture for the Dayak Community in Buntut Bali Village, Malan Island District, Katingan Regency. Data analysis techniques, the authors use descriptive analysis as follows: data collection, data reduction, data presentation or data display then draw conclusions or data verification. The results of this study are the origins of Manugal Culture for the Dayak community, Buntut Bali Village, Malan Island District, Katingan Regency, which is the custom of their ancestors which was passed down from generation to generation by former people until now, it is still maintained by the Dayak people.